(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The glutathione-S-transferases (GSTs) comprise a class of enzymes that detoxify carcinogenic compounds by conjugating glutathione to facilitate their removal. Polymorphisms in glutathione S-transferase Omega 1,2 (GSTO1, GSTO2), and GSTP1 genes have been related to risk for bladder cancer. Objective:To assess a comprehensive picture of the relationship between smoking and GSTO2 gene Asn142Asp variant (rs156697) with bladder cancer Methods:A case control study was conducted at Chemistry and Biochemistry Department, College of Medicine and DNA Research and Training Center, Al-Nahrain University from February 2014 to September 2014. Forty one bladder cancer patients and 41 age matched apparently healthy controls were participated in this study. Genotyping of the GSTO2 Asn142Asp polymorphism was evaluated using a polymerase chain reaction fragment length polymorphism (PCR-RFLP) method. The odds ratio (OR) and 95% confidence interval (CI) were calculated as a measure of the combined effect of cigarette smoking and the GSTO2 Asn142Asp polymorphism on bladder cancer risk. Result:It was found that subject with the GSTO2 Asp/Asp genotype have significantly increased bladder cancer risk (OR 4.92; 95% CI =1.32 - 18.30). A statistically highly significant increased the bladder cancer risk was also found in ever smoker of the GSTO2 (Asn/Asn) (OR =11.8; 95% CI=2.43 - 57.84) and (Asn/Asp +Asp/Asp) (OR =12.8; 95% CI=3.23 - 51.41) compared with never smoker Ala/Ala genotype. Conclusion:The study suggests that smokers having GSTO2 Asn/142Asp polymorphism could play an important role as risk factor for the development with bladder cancer. Keywords :Bladder cancer, single nucleotide polymorphism, glutathione S-transferase, GSTO2, Asn142Asp, smoking, rs156697.